2015
DOI: 10.1177/0194599815573726
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Reconstruction Experience and Outcomes at a Low‐Volume Institution over 20 Years

Abstract: Free flap reconstruction of the head and neck can be performed by appropriately skilled surgeons with acceptable outcomes in low-volume settings. Success rate appears to increase as clinical experience is gained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In the previous studies the annual operation rate has varied between 14-38. 3,7,8 However, the annual complication rate cannot be explained by this due to heterogeneity of the classification of the complications. Also Klosterman et al did not find differences in complication rates between low-volume and high-volume centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous studies the annual operation rate has varied between 14-38. 3,7,8 However, the annual complication rate cannot be explained by this due to heterogeneity of the classification of the complications. Also Klosterman et al did not find differences in complication rates between low-volume and high-volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…Also Klosterman et al did not find differences in complication rates between low-volume and high-volume centers. 3 Previous studies have found that smoking, comorbidity and advanced age are potential risk factors for postoperative complications after free flap surgery for cancer of the head and neck . 2,6,7 In our study, we did not find a significant correlation between these factors and complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Take‐back rates increased 7.2 times for transfused patients. Take‐back percentage varies in the HN literature, ranging from 2% to 16% . Hematoma formation causing flap take‐back leads to acute blood loss itself or additional blood loss from the subsequent surgery, making transfusion more likely.…”
Section: Discussionmentioning
confidence: 99%
“…Take-back percentage varies in the HN literature, ranging from 2% to 16%. 5,7,8 Hematoma formation causing flap take-back leads to acute blood loss itself or additional blood loss from the subsequent surgery, making transfusion more likely. Indeed, even intraoperative transfusion has been associated flap take-back.…”
Section: Discussionmentioning
confidence: 99%